Comparative analysis of two CBN grinding wheels performance in nodular cast iron plunge grinding - de Martini Fernandes, Lucas [UNESP] (2018)
The extensive tribological use of nodular cast iron in ground transport industry, e.g., trains and automobiles, has brought growing scientific interest. The various applications of this material are due to the versatility of mechanical properties without adding alloy elements, making possible to achieve good results varying just the heat treatment. Due to its high fluidity, workpieces made of this material can be produced with final dimensions and shapes very close to the designed ones, making necessary just the use of finishing machining operations to get the final dimensions, more specifically those concerning the grinding process. To optimize cost production, machining processes became the focus of scientists and engineers. The grinding wheel can determine the success of an operation as its properties influence productivity and workpiece quality decisively. This work analyzes the grinding process of the ductile iron GGG-70 (average hardness of 270 HB) using two types of vitrified bonded CBN grinding wheels, which have as their only distinction the marked difference in friability of the abrasive grains. The performance of each grinding wheel will be analyzed taking into account the output parameters values obtained from surface roughness, average power, diametric wear of the grinding wheel, microstructure of the ground surfaces, and microhardness measures from the ground surface to the center of the workpiece. It was observed that the less friable wheel produced, regarding the average surface roughness, values of 0.27, 0.30, and 0.36 μm for the feed rates of 0.5, 1.0, and 1.5 mm/min, respectively, and, regarding the diametric wheel wear, produced values of 2.52, 2.99, and 4.01 μm for the same feed rates, respectively. On the other hand, when using the more friable wheel, average surface roughness values of 0.33, 0.44, and 0.64 μm and diametric wheel wear values of 3.21, 4.22, and 7.24 μm were obtained. In this way, the less friable wheel showed better results for all the conditions. Considering the feed rate order of 0.5, 1.0, and 1.5 mm/min, the improvement in surface roughness was about 18.18, 31.82, and 43.75%, respectively, and the reduction of the wheel wear was about 21.50, 29.15, and 44.61%.